Penerapan Unsur-Unsur Pendidikan Kristen dalam Perjamuan Kudus Anak sebagai Upaya Pembentukan Kecerdasan Spiritual - Justin Niaga Siman Juntak; Yohanes Ayom Prabawani; Sabda Wahyudi; Eliana Setyanti; Kristriyanto (Harati: Jurnal Pendidikan Kristen, 2024)
The Holy Communion is a part of faith maintenance. GKJ Jambeyan has implemented Holy Communion for children who have not yet taken the confirmation, or in other words, for teenagers who have not yet professed their faith. There are two teenagers who often cause trouble even after participating in Children's Communion, such as using foul language and harming others. Additionally, parents of two teenagers from GKJ Jambeyan have expressed concerns about their children being difficult to manage and burdensome. Moreover, one of these two teenagers withdrew from fellowship, even though they had attended Children's Communion, during which they received guidance on living as Christians. However, one of the teenagers experienced a positive change in daily behavior, making the spiritual transformation among these teenagers an interesting subject for research. This study uses a quantitative method to examine the existing correlation. The results of this study show that the application of educational elements in Children's Communion has a 93.7% impact on the spiritual intelligence of teenagers at GKJ Jambeyan. Furthermore, if there is an increase in the spiritual intelligence of GKJ Jambeyan teenagers, there is a 90.7% increase in the application of educational elements in Children's Communion.